Iron-Catalyzed Oxidative Radical Alkoxycarbonylation of Activated Alkenes with Carbazates toward Alkoxycarbonylated Benzimidazo[2,1-a]isoquinolin-6(5H)-ones - Tang, Yucai; Li, Min; Huang, Hongxin; Wang, Feifei; Hu, Xia; Zhang, Xiangyang (Synlett, 2021)
A FeCl2·4H2O-catalyzed oxidative alkoxycarbonylation of activated alkenes with carbazates toward alkoxycarbonylated benzimidazo[2,1-a]isoquinolin-6(5H)-ones has been established. The reaction proceeded smoothly to furnish a series of structurally diverse benzimidazo[2,1-a]isoquinolin-6(5H)-one frameworks in moderate to good yield.
Keywords: iron catalysis; carbazates; hydrazinecarboxylates; alkoxycarbonylation; benzimidazoisoquinolinones; alkenes